Mary Shelley - Brackett, Virginia (Ipswich, Massachusetts : Salem Press, a division of EBSCO Information Services, Inc. ; Amenia, NY : Grey House Publishing, 2016)
"Best known as the author of the ubiquitous Gothic novel, Frankenstein; or, The Modern Prometheus, Mary Shelley lived an eventful, though grief-stricken life, between troubled finances, her father's disownment, and the death of multiple children. Topics discussed in this compilation include autobiographical elements and themes in her work, the influence of Frankenstein today, and her relationship with her husband, Romantic poet-philosopher Percy Bysshe Shelley."--Book description, Amazon.com.
About This Volume / Virginia Brackett -- On Mary Shelley / Virginia Brackett -- Biography of Mary Shelley / Michael Flaherty -- Creations Born of Chaos: The Historical and Cultural Context of Mary Shelley's Novels / Calinda C. Shely -- "Odious Handywork": Reception as Reconciliation and the Critical Legacy of Mary Shelley / Danielle Barkley -- "I ate no apple": An Analysis of Gender, Power, and Blame in Mary Shelley's Early Fiction / Stacey L. Kikendall -- Neglect and Childhood Trauma in Frankenstein and Wuthering Heights: Writing the Domestic (Abuse) Novel / Katherine Montwieler -- "We shall be monsters, cut off from all the world": Mary Shelley and Disability Studies / Dwight Codr -- Not "merely weaving a series of supernatural terrors": Mary Shelley Critiques Women's Education in Anxiety / Robin Runia -- Dr. Frankenstein and the Review Board: Research Ethics in Frankenstein / Ashley Lynn Carlson -- "But Again the Frost Came": The Arctic Canvas in Mary Shelley's Frankenstein / Nicole Papas -- Environment, Ecology, and Apocalypse in Mary Shelley's The Last Man / Seth T. Reno -- Monstrous Crimes and Offender Accountability: Shelley's Representation of Criminal Justice from Frankenstein to Falkner / Colleen Fenno -- "The Invisible Girl": Gender and Form in Mary Shelley's Short Stories / Nicole Lobdell -- Mary Wollstonecraft Shelley--The Immortal Mortal: A Psychoanalytic Analysis of The Last Man, "On Ghosts," and "The Mortal Immortal" / Katherine Marie Alexander -- Mary Shelley and Romantic Medievalism / Christine E. Kozikowski -- "It's Alive": Popular Culture Commodification of Frankenstein's Monster / Natalie Neill -- Chronology of Mary Shelley's Life -- Works by Mary Shelley -- Bibliography.
Includes bibliographical references (pages 257-266) and index.
Keywords: Shelley, Mary Wollstonecraft, -- 1797-1851 -- Criticism and interpretation; English fiction -- 19th century -- History and criticism; Monsters in literature; English fiction; 1800-1899; Criticism, interpretation, etc